2015
DOI: 10.1016/j.vetmic.2015.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Live poultry market workers are susceptible to both avian and swine influenza viruses, Guangdong Province, China

Abstract: Guangdong Province is recognized for dense populations of humans, pigs, poultry and pets. In order to evaluate the threat of viral infection faced by those working with animals, a cross-sectional, sero-epidemiological study was conducted in Guangdong between December 2013 and January 2014. Individuals working with swine, at poultry farms, or live poultry markets (LPM), and veterinarians, and controls not exposed to animals were enrolled in this study and 11 (4 human, 3 swine, 3 avian, and 1 canine) influenza A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 30 publications
3
22
0
Order By: Relevance
“…Our cohort study did not reveal any differences in the risk of contracting H9N2 virus between the swine workers and the general population, which is consistent with a previous study's findings . Indeed, the poultry workers had a higher risk than the general population of contracting an H9N2 infection, similar to that reported previously . The higher risk of infection with H9N2 virus among poultry workers suggests that increased exposure to poultry would heighten the risk of contracting this virus.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our cohort study did not reveal any differences in the risk of contracting H9N2 virus between the swine workers and the general population, which is consistent with a previous study's findings . Indeed, the poultry workers had a higher risk than the general population of contracting an H9N2 infection, similar to that reported previously . The higher risk of infection with H9N2 virus among poultry workers suggests that increased exposure to poultry would heighten the risk of contracting this virus.…”
Section: Discussionsupporting
confidence: 91%
“…11 Second, our study did not involve workers from live poultry markets, because these markets were banned in Beijing after 2005, but the participants in some of the other serological studies on H9N2 AIV included live poultry market workers. Furthermore, a cross-sectional, seroepidemiological study conducted in Guangdong Province showed that the seroprevalence of anti-H9N2 antibodies in the poultry market workers was much higher than in the poultry farm workers and veterinary staff, 40 of another study. 41 Third, people in the southern provinces prefer to eat fresh rather than frozen poultry, and this increases their exposure to the virus.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…33 , 34 These differences between China and Bangladesh play an important role on the prevalence of different species within the live bird markets, as well as the prevalence of various subtypes of IAVs found and what impact this may have on public health. Despite these differences, the detection rate of AIVs in Bangladesh is relatively high (24%) compared to both Egypt (5%) 35 and China (4%), 36 which further emphasizes the need for both continued surveillance and implementation of standard precautions against IAV transmission and infection.…”
Section: Discussionmentioning
confidence: 99%
“…in LPM enhances the reassortment potential of AIV. Close contact between humans and the LPM provides conditions for cross-species AIV transmission2829. For instance, most of the H7N9 infected humans had prior exposure to LPM, which was identified as the source of human H7N9 infection cases3031.…”
Section: Discussionmentioning
confidence: 99%